Pengaruh Kualitas Pelayanan, KepuasanPelanggan, Dan Citra Perusahaan TerhadapLoyalitas Pelanggan Di Supermarket SuperindoAdisucipto - Indriyani, Eka Candra; , Ir.Irmawati, S.E., M.Si (2017)
This study aims to determine the effect of service quality, customer satisfaction, and corporate image on customer loyalty in the Adisucipto Superindo Supermarket. The sample used is the consumer who shopped at the supermarket Superindo Adisucipto by distributing 150 questionnaires and 137 questionnaires were returned. These results indicate that service quality, customer satisfaction, and corporate image significantly affect customer loyalty. Test the validity of the instrument by comparing the value of r count r table for degree of freedom d (f) = n -k with an alpha of 0.05. while the reliability test using Cronbach Alpha. The study found that: (1) The service quality has a positive effect on customer loyalty in the Adisucipto Superindo Supermarket evidenced by the t value of 1,992 and the probability value of 0.048 < 0,05. (2) Customer satisfaction has a positive effect on customer loyalty in the Adisucipto Superindo Supermarket evidenced by the t value of 4,123 and the probability value of 0.000 < 0,05. (3) The image of the company has a positive effect on customer loyalty in the Adisucipto Superindo Supermarket evidenced by the t value of 4.376 and the probability value of 0.000 < 0,05. This research also obtained the value of Adjusted R Square of 0.383, it means that 38.3% of consumer loyalty variables can be explained by the independent variable, quality of service, customer satisfaction, corporate image, while the remaining 61.7% is explained by varianother variable outside this research.